Combination effect of doxorubicin and HIF inhibitor on MCF-7 CD44+/CD24- subpopulation cells in hypoxic condition - Azadeh Rasouli; Shima Aliebrahimi; Vahideh Montazeri; Mohammad Hossein Ghahremani; Seyed Nasser Ostad (Universidade de São Paulo, 2022)
Abstract Hypoxia-inducible factors (HIFs) and cancer stem cells (CSCs) are two challenging causes of radiotherapy and chemotherapy resistance, leading to most cases of failure and recurrence in breast cancer therapy. This study was conducted to investigated the inhibitory effect of combination therapy with doxorubicin (an anthracycline) and FM19G11 (an HIF inhibitor) on MCF-7 cells and their CSC-like cells (CSC-LCs). MCF-7 CSC-LCs with a CD44+/CD24- phenotype were sorted and characterized by flow cytometry. A combination of doxorubicin and FM19G11 caused more cytotoxic effects on MCF-7 and CSC-LCs compared to doxorubicin monotherapy. The largest synergistic effect was observed in CSC-LCs under hypoxic conditions; however, MCF-7 cells showed no synergism in normoxic conditions. The administration of doxorubicin and FM19G11 induced late apoptotic and necrotic cell death in MCF-7 and CSC-LCs. Additionally, G2 phase arrest was observed in both cells. Our results demonstrated that co-administration of FM19G11 and doxorubicin had a synergistic effect in hypoxia and improved drug resistance in breast cancer stem cells.